The Relationship of Theory of Mind with Working Memory and Problem Solving In Students: The Mediating Role of Emotional Intelligence - Elahe Shirovi; Shekoofeh Mottaghi; Azra Mohammadpanah Ardakan (پژوهش‌های علوم شناختی و رفتاری)
The present study aimed to examine the mediating role of emotional intelligence (EI) in the relationship between theory of mind (ToM) and executive functions, specifically working memory and problem-solving. A correlational research design with structural equation modeling (SEM) was employed. The study population comprised female students aged 14 to 18 years in Khomeini Shahr (2021), from which 300 participants were selected using a convenience sampling method. The assessment instruments included an emotional intelligence questionnaire and software-based tests for the Tower of London task, working memory, and a mind-reading test using eye-image stimuli. The findings indicated that ToM exerted a positive, significant direct effect on EI (β = 0.233), working memory (β = 0.318), and problem-solving (β = 0.299) (p < 0.01). Furthermore, EI had a significant direct effect on working memory (β = 0.219) and problem-solving (β = 0.319) (p < 0.01). The indirect effect of T0M on working memory and problem-solving, mediated by EI, was β = 0.036 and β = 0.062, respectively. These results confirm the mediating role of EI in the association between T0M and executive functions. The findings underscore the pivotal role of ToM and EI in enhancing cognitive functions, suggesting that interventions aimed at strengthening these abilities could improve students' executive functioning.IntroductionExecutive functions are higher-order cognitive and metacognitive processes that facilitate goal-directed behavior by enabling individuals to manage their thoughts, emotions, and actions. These functions encompass a range of advanced abilities, including inhibition, strategic planning, self-initiation, cognitive flexibility, and impulse control (Di-Tella et al., 2020). Among these, problem-solving is regarded as a core component, representing an intelligent, rational, and goal-oriented activity that reflects the highest levels of human cognitive functioning (Güven et al., 2019). Working memory, another critical aspect of executive functions, is responsible for the temporary storage and manipulation of information necessary for executing complex cognitive tasks, such as reasoning, comprehension, learning, and mental retention (Major & Tet, 2019). Impairments in executive functions can significantly affect cognitive, emotional, and social performance, resulting in a range of challenges across personal, academic, and interpersonal domains (Craven, 2023).Theory of mind (ToM), a crucial cognitive skill, enables individuals to understand others' mental states, including beliefs, desires, and emotions, facilitating successful social interactions and adaptive behavior (Ruffman, 2014). Research demonstrates the role of ToM in enhancing self-regulation, problem-solving skills, executive control processes, and the interpretation of ambiguous stimuli. It also contributes to success in learning, academic achievement, social competence, interpersonal skills, and emotion management (Doenyas et al., 2018; Lackner et al., 2010; Wang et al., 2017).Despite these insights, no studies to date have investigated the interconnected relationships between ToM, emotional intelligence (EI), and executive functions. Prior research has highlighted links between ToM and EI, while EI has also been shown to influence executive functions. Building on these findings, the present study aims to investigate the mediating role of EI in the relationship between ToM and executive functions, offering new insights into the cognitive and emotional mechanisms underlying executive functioning. MethodThe present study employed a descriptive-correlational design. The statistical population consisted of all female students between the ages of 13 and 18 in Khomeini Shahr during the academic year 2019–2020. A total of 300 participants were selected using convenience sampling. The inclusion criteria required that the participants did not suffer from epilepsy, possessed normal intelligence within the typical range for their age group, and were right-handed, as determined through a pre-test interview. The exclusion criteria included unwillingness to continue participation, carelessness in performing the tasks, or failure to complete the tests.The research tools included the Schutte Self-Report Inventory (SSRI) for Emotional Intelligence, the Tower of London Test (TOL) for problem-solving ability, the N-back test for working memory, and the Reading the Mind in the Eyes Test (RMET) to assess theory of mind. The collected data were analyzed using AMOS-23 and SPSS-23 software through the structural equation modeling (SEM) approach. FindingsAccording to Figure 1, which presents the conceptual model of the research, theory of mind (ToM) serves as an exogenous variable, while working memory and problem-solving act as endogenous variables. The model's fit indices indicate an acceptable level of fit, demonstrating that the conceptual model aligns well with the data (χ²/df= 2.135, RMSEA= 0.076).The results showed that ToM exhibited a positive and significant direct effect on working memory and problem-solving (p < 0.01). Similarly, emotional intelligence (EI) displayed a positive and significant direct effect on both working memory and problem-solving (p < 0.01). Furthermore, ToM indirectly influenced working memory and problem-solving through the mediating role of EI. These findings confirm the partial mediating role of EI in the relationship between ToM and both working memory and problem-solving. Figure 1: The relationship of theory of mind with working memory and problem solving with the mediating role of emotional intelligenceDiscussion and ConclusionThe findings indicate a direct, significant, and positive relationship between theory of mind (ToM) and working memory. Mastery of false-belief tasks reflects progress in key memory processes, including source monitoring, metamemory, and representation. In these tasks, false belief plays a critical role because it allows individuals to distinguish between reality and their mental representation of it (Carlson et al., 2015).The study also revealed a positive and significant relationship between ToM and problem-solving ability. By enhancing social cognition and information processing skills, ToM strengthens an individual's capacity for effective problem-solving (Wang et al., 2017). Furthermore, a significant relationship between ToM and emotional intelligence (EI) was observed. As ToM develops, individuals become more adept at integrating emotional and social knowledge to interpret complex situations (Qualter et al., 2011).Another key finding was the direct, significant relationship between EI and working memory. Neurobiological evidence suggests an overlap between EI and working memory, as both are associated with the prefrontal cortex. Emotional intelligence not only influences the brain's processing of emotional stimuli but also affects cognitive tasks such as working memory (Mavrou, 2021). Additionally, the results confirmed a positive and significant causal relationship between EI and problem-solving ability. Individuals who possess problem-solving skills and apply them in daily life experience lower psychological stress (Korkmaz et al., 2020).The study further demonstrated that ToM significantly influences working memory through the mediating role of EI. Working memory functions as the cognitive engine of the mind, enabling individuals to retain and manage information. It plays a crucial role in learning, reasoning, and comprehension (Baddeley, 2020; Major & Tetley, 2019). Higher levels of EI likely enhance reasoning and recall abilities, which are integral to working memory.Moreover, the findings highlight the role of emotional regulation in cognitive performance. When emotional control is lacking, the neocortex—the brain region responsible for logical thinking—becomes less active, while the midbrain, which processes emotions, dominates. This shift can impair concentration and cause individuals to respond impulsively (Gültekin & Icigen, 2019). As a result, emotional regulation is essential for managing stress, solving problems effectively, and maintaining focus in challenging situations.One limitation of the current study was that it was conducted during the COVID-19 pandemic, necessitating the use of convenience sampling instead of random sampling. Given the cross-sectional nature of the study, it is recommended that future research explore these relationships longitudinally to determine how they evolve across different age groups.